Serum Homer1 is a Novel Biomarker for Predicting the Clinical Outcomes of Acute Ischemic Stroke Patients [Letter] - Tammasse J (Dove Medical Press, 2024)
Jumraini Tammasse Department of Neurology, Faculty of Medicine, Hasanuddin University, Makassar, IndonesiaCorrespondence: Jumraini Tammasse, Department of Ophthalmology, Faculty of Medicine, University of Hasanuddin, Perintis Kemerdekaan Road Km.10, Makassar, Indonesia, Email jumraini@med.unhas.ac.id